Investigation of Micron-Scale Radiotherapy Dose Deposition in the Lung: Effect of Magnetic Field and Nanoparticles—a Monte Carlo Simulation - Montinola, Denxybel; McNamara, Aimee L.; Kuncic, Zdenka; Byrne, Hilary L. (Frontiers in Physics, 2022)
MRI-Linacs couple magnetic resonance imaging (MRI) with a linear accelerator (Linac) to enable MR-guided radiotherapy. The magnetic field is known to cause inhomogeneities in the pattern of dose deposition at centimeter-scale air-tissue interfaces such as pockets of digestive gas but has not been studied at the micrometer scale of lung alveoli. Nanoparticle radio-enhancement is a novel therapy enhancing the dose deposition pattern where nanoparticles are delivered to the radiation target, with proposed application to lung cancer treatment through inhalation of nebulized nanoparticles. This study reports the first investigation of the effect of a magnetic field on the pattern of dose deposition at the micrometer air-tissue interfaces of alveoli in the lung, and the impact of incorporating nanoparticles. Monte Carlo simulations investigated a single alveolus model irradiated with mono-energetic, uni-directional electrons and a multi-alveoli model irradiated with a realistic beam at depth. The magnetic field was found to produce field-strength dependent hot- and cold-spot dose inhomogeneities in the tissue surrounding a micrometer air cavity irradiated with low energy (100 keV) electrons. The most affected regions exhibited a dose increase of 37.30 ± 1.29% and a decrease of 31.58 ± 1.01% with the application of a 1.5 T magnetic field. The addition of nanoparticles to the interior surface layer of the alveolus air cavity increased energy deposit by a constant ratio dependent on the nanoparticle concentration regardless of magnetic field strength. A similar but less pronounced effect was observed for a multi-alveolus model irradiated at depth by a 6 MV photon beam. This result warrants further investigation into the biological impact of micrometer-scale dose inhomogeneity on tumor response and normal tissue complication probability.